La Formación Profesional: nuevos y viejos problemas (Journal of Parents and Teachers, 2014)
The article deals with all those factors that allow understanding the paradox of Professional Training in Spain. Thus, the author analyzes why, despite being one of the best options and with the highest demand, it is the one that reaches the lowest percentage. The key points to understand this issueare theway the law contemplates this training as well as the lack of motivation of the students who access it. All this impedes progress in learning and harms the system and its students. In addition, the author presents the difficulties in the labor market as well as the changes introduced by new laws. Current problems such as the controversy between the Baccalaureate and Professional Training or the lack of flexibility in terms oflabor demand are also analyzed. Finally, the author underlines the vital improvement of the system where this training acquires the value and recognition it deserves.
Keywords: Professional training, education, Secondary education